ANALYSIS OF LAND USE AND DISCRETION BASED ON ENVIRONMENTAL GEOLOGICAL PARAMETERS BY APPLYING ANALYTICAL HIERARCHY PROCESS AND OVERLAY METHODS FOR TANJUNG LESUNG REGION, PANIMBANG DISTRICT, PANDEGLANG REGENCY, BANTEN PROVINCE - Akbar Mohammad Arif, Gema
Tanjung Lesung is one of the strategic areas that are included as one of the 10 Priority Tourism Destinations which includes the Tanjung Lesung Special Economic Zone (SEZ). The development plan for the Tanjung Lesung Area requires discretion analysis based on environmental geological concepts and evaluation of land use. This study aims to determine the zoning of land space and provide recommendations for land use. The research area is located at coordinates 9286000 – 9276000 mN and 570000 – 575000 mE (UTM WGS 1984 Zone 48S) administratively located in Panimbang District, Pandeglang Regency, Banten Province with 34,3 km² wide area. The methods used in this research are literature study, field mapping, petrographic analysis, clean water laboratory examination analysis, and environmental geology analysis using Analytical Hierarchy Process (AHP) method. The assessment component used in the environmental geology analysis is divided into components of geological resources (rock/soil carrying capacity, hillside slope, groundwater conservation zone, aquifer productivity, groundwater depth, groundwater suitability as drinking water), geological hazards (disaster-prone areas of earthquake, tsunami, volcano and vulnerability zones of soil movement), nongeological (Distance from coastal borders, flood areas, road facilities, and swamps), as well as the restraint component (beach frontier, river border, high vulnerability zones of soil movement and airfield). The data used in this research come from thematic maps, rock samples, and water samples compiled and digitized to result in overlayed parameter maps of environmental geology. Environmental geology analysis shows that Tanjung Lesung Tourism Area recommended for the development of areas with its percentage of area is Suitable Zone (51,2%), Slightly Suitable Zone (38,2%), Fairly Suitable Zone (0,6%). The zone not recommended is the Nonsuitable Zone (10%). The environmental geology analysis shows that the zoning of land space is in the Suitable Zone (51.2%), Slightly Suitable Zone (38.2%), Fairly Suitable Zone (0.6%), and the Nonsuitable Zone (10%). The results from the evaluation of the suitability of land use for the Cultivation Area in the RTRW Kab. Pandeglang 2011-2031 shows that the residential area is still in the Slightly Suitable Zone (the Suitable Zone has not been optimized), the plantation area is actually in the Suitable Zone, and the tourism area is in the Slightly Suitable – Nonsuitable Zone. Tourist Areas in the Nonsuitable Zone are located along the coastal border.